Strategi Pemulihan Omzet UMKM Pasca Pandemi di Kota Parepare - A. Rio Makkulau Wahyu; Wirani Aisiyah Anwar; Eliza Andriani; St. Hajar Putri (Universitas Islam Negeri Alauddin Makassar, 2023)
Reduced community activity and mobility due to the policy for handling the Covid-19 pandemic, has hampered the pace of MSME business activities in the city of Parepare. This has had an impact on a drastic decrease in the income turnover of these MSME business actors. This study uses a qualitative approach with the aim of producing some findings on the MSME turnover recovery strategy in the city of Parepare by using data sources obtained from informants from MSME actors and the Parepare city government, in this case the Parepare City Trade Office, as well as analyzing several scientific literature studies that discuss same problem. The results of this study indicate that there has been a decrease in MSME turnover in the city of Parepare by 73.50%, therefore a turnover recovery strategy is needed that can be implemented immediately, including through employment strategies, production strategies, financial strategies, and marketing strategies. This is an alternative strategy that can be applied to MSME players in the city of Parepare in recovering turnover after the Covid-19 pandemic has passed.